KAMPUNG PECUT” WEBSITE AS A MEANS OF CULTURE PROMOTION IN THE DIGITAL ERA - Andi Basuki; Etty Soesilowati; Siti Mas’ula; Muhammad Aris Ichwanto; Dewi Ayu Sakdiyyah; I Wayan Bayu Wiarta (International Journal of Engagement and Empowerment, 2022)
Packaging Village, Kediri City District is one of the areas in Kediri City, which is famous for its cultural arts village, especially Jaranan. So many people know it as the "Kampung Pecut." The branding of the "Kampung Pecut" has been carried out, primarily through various performances held to introduce "Pecut" arts and "Pecut" crafts. However, the Covid-19 pandemic has limited promotional activities due to a ban on holding shows. It causes an economic downturn for the arts and "Pecut" craftsmen. So as an effort to overcome this problem, the community service team conducts training and assistance to optimize the sale of "Pecut" handicrafts and the completeness of the art of “Jaranan” through digital media. Based on the results of the joint evaluation, information obtained that this mentoring activity was constructive for art actors to increase their ability to promote"Pecut” arts and "Pecut" crafts to the broader community. So that is expected to improve the economy of the art performers. After the mentoring process is deemed sufficient by paying attention to the evaluation results and seeing the use of media directly, the direct mentoring process stops. However, indirect assistance (monitoring and communication) continued to develop and implement to obtain maximum results and maintain the sustainability of the technology used